Actual Problems of Antimonopoly Control of the Government and Municipal procurements of Services of Vocational Education - Vadim Valeryevich Vladimirov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article questions of purchases of services of vocational education (on the example of purchases of services in training of specialists in the sphere of purchases for the state and municipal needs) from the point of view of antimonopoly control of such purchases are considered. The characteristic mistakes made by the state and municipal customers during purchases of services of vocational education are investigated. The recommendations about implementation of such purchases promoting achievement of the objectives, provided by p. 1 of art. 1 of the Federal law of 05.04.2013 N 44-FZ «About contract system in the sphere of purchases of goods, works, services for ensuring the state and municipal needs» are made.